2019
DOI: 10.1016/j.isci.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Extract Improves Obesity through Regulation of the Gut Microbiota and Bile Acids via Pathways Involving FXR and TGR5

Abstract: Summary The metabolic improvement effect of blueberries has long been recognized, although its precise mechanism(s) remains obscure. Here, we show that phenolic blueberry extract (BE) treatment improved diet- and genetically induced metabolic syndromes, which were linked to increased energy expenditure in brown adipose tissue (BAT) and improved lipid metabolism in the liver via pathways involving the bile acid (BA) receptors TGR5 and FXR. These observations were strongly correlated with the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 35 publications
7
98
2
1
Order By: Relevance
“…Since the limited absorption and utilization of dietary polyphenols makes it difficult for polyphenols and metabolites in the blood to function, [ 16,26 ] many studies have shown that polyphenols exert anti‐obesity and anti‐inflammatory function through regulating GM. Grape seed proanthocyanidin extract (GSPE) ameliorated inflammation and adiposity in HFD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the limited absorption and utilization of dietary polyphenols makes it difficult for polyphenols and metabolites in the blood to function, [ 16,26 ] many studies have shown that polyphenols exert anti‐obesity and anti‐inflammatory function through regulating GM. Grape seed proanthocyanidin extract (GSPE) ameliorated inflammation and adiposity in HFD mice.…”
Section: Discussionmentioning
confidence: 99%
“…The composition and concentration of the BAs in the plasma were determined through UPLC/electrospray ionization mass spectrometry (UPLC/ESI‐MS), as described previously with some modifications. [ 16 ] Briefly, 1 mL precooling ethanol was added to a 50 µL plasma sample, followed by vortexing and centrifugation. The supernatant was then filtered through a 0.22 µm filter before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Library preparation for transcriptome sequencing: A total amount of 3 μg RNA per sample was used as input material for the RNA sample preparations. Sequencing libraries were generated using the RNA Library Prep Kit for Illumina (NEB, USA) and index codes were added to attribute sequences to each sample, as previously described 26 . (3) Clustering and sequencing: The clustering of the index‐coded samples was performed on a cBot cluster generation system using TruSeq PE Cluster Kit v3‐cBot‐HS (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…In our present study, metabolomics data showed that TUDCA in the intestinal contents of the HFD + Met group increased significantly. Previous studies revealed that metformin treatment increased the levels of the conjugated bile acid in the gut by decreasing the abundance of species of Bifidobacterium and its bile salt hydrolase (BSH) activity in the intestines of individuals with T2D 17,30,31 . Bile salt hydrolase, secreted by intestinal bacteria, decomposes TUDCA in the intestine and metabolizes TUDCA to taurine and UDCA.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids (BAs), which are produced in the liver and serve as important ingredients of the digestive fluid in the intestine, enter the small intestine through the biliary system and participate in fat digestion and absorption 15,16 . Gathered evidence demonstrates that BAs could improve the intestinal homeostasis by modulating the gut microbiota, thus relieving metabolic syndrome 17 . Recent studies also suggest that BAs can participate in the liver-gut axis circulation and the improvement of HFD-initiated metabolic disorders by inhibiting the proliferation of pathogenic bacteria 18,19 .…”
Section: Introductionmentioning
confidence: 99%